Modified biochar from waste biomass for the efficient removal of heavy metals in industrial wastewater: A review - Wan Noni Afida, Ab Manan; Ahmad Zamani, Ab Halim (Penerbit Universiti Malaysia Pahang, 2024)
Due to advancements in society and industry, the problem of heavy metal contamination in water is becoming increasingly severe. Despite being a cost-effective and eco-friendly adsorbent for heavy metal ions, biochar's efficiency in adsorption and immobilisation needs further enhancement. Modified biochar, an enhanced iteration of biochar, has garnered significant interest among the scientific community. This article provides a concise overview of the latest advancements in treating heavy metal pollution in water through the utilisation of biochar. The discussion focused on the features and benefits of various biochar modification processes, including physical modification and chemical modification of biochar. A summary was made of the process by which modified biochar is used to eliminate heavy metals from water. The study revealed that biochar exhibited enhanced performance following modification, resulting in increased surface areas and a greater number of functional groups. Additionally, it demonstrated sufficient binding sites to effectively bind heavy metal ions. Biochar has great potential as a viable solution for the remediation of heavy metals in the environment. Nonetheless, the emphasis continues to be on the advancement of modified biochar that demonstrates high efficiency and cost-effectiveness, featuring a significant sorption capacity, outstanding photocatalytic performance, and environmentally acceptable characteristics that prevent secondary pollution.